Exploring the impact of the COVID-19 safety measures on learner-centred teaching in rural English FAL classrooms - Mokoena, Mosebetsi (Journal for Language Teaching, 2022)
The Coronavirus (COVID-19) has disrupted the process of teaching and learning in unprecedented ways. There has been a shift in the way lesson presentation takes place in many classrooms. In particular, the COVID-19 safety measures (social distancing and wearing of masks) threaten learner-centred teaching in rural English FAL classrooms. As a result, there is a need to explore the impact of the COVID-19 safety measures on learner-centred teaching in rural English FAL classrooms. To achieve this aim, the study raises these questions: how do COVID- 19 safety measures disrupt learner-centred teaching in rural English FAL classrooms? How do rural English FAL teachers implement learner-centred teaching while adhering to the COVID-19 safety measures? The study adopts a qualitative research design and uses Document Analysis and Online interviews to generate data from eleven participants. Following thematic analysis, data revealed that the COVID-19 safety measures negatively impact learner-centred teaching in rural English FAL classrooms. The challenges include: ineffective monitoring and scaffolding, difficulty engaging in concrete and cooperative learning, limited opportunities for creativity, and distorted communication. In response, the paper recommends various strategies to lessen the impact of the COVID-19 safety measures on learner-centred teaching in rural English FAL classrooms. These include: strengthening the home-school connection, creating a supportive classroom environment, incorporating fun activities in collaborative learning activities, and providing activities that encourage independent learning.